ANALISIS EFEKTIVITAS SISTEM PENGENDALIAN INTERN PENERIMAAN DAN PENGELUARAN KAS PADA PERUMDA TUGU ANEKA USAHA KOTA MALANG - Wijayanti, Rika; Eloi Kristanti, Lydia Clarissa (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2024)
Purpose: This study aims to analyze the effectiveness of the implementation of internal control elements to cash receipts and disbursements at Perumda Tugu Aneka Usaha Malang City. The effectiveness of the internal control system implementation is assessed based on the guidelines of Government Regulation of the Republic of Indonesia Number 60 of 2008 concerning the Government internal control system which consists of five indicators of SPIP elements. This type of research is descriptive qualitative research using data collection methods in the form of interviews and documentation. Primary data sources were obtained through interviews with research informants, while secondary data were obtained from documents related to the research topic. The results showed that Perumda Tugu Aneka Usaha Malang City has implemented an internal control system over cash receipts and disbursements effectively in accordance with the components contained in PP RI Number 60 of 2008, but in its implementation it was still found that several divisions were handled out by 1 (one) person, which means that there are positions that are carried out by 1 person or called concurrent positions. Authorization has also not been carried out effectively because the Cash Expenditure Treasurer Section still violates the company's SOP rules by issuing money first without waiting for the Payment Request Letter. The results in this study are expected to help company management to immediately complete the company's organizational structure and be more assertive in providing direction to each position function so that it can carry out its authorization in accordance with procedures.